PERAN KEBIJAKAN PEMBANGUNAN TERPADU DALAM MENGURANGI RESIKO BENCANA - Azizah Kusuma Dewi; Hylda Sasdar (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2024)
The research method approach using literature involves exploiting written sources of information such as scientific journals, books, research reports and mass media and other official documents. The research method used is a disaster risk assessment to identify threats and vulnerabilities in coastal areas. This study discusses the role of integrated development policies in disaster risk reduction. An integrated development policy is a comprehensive approach to managing natural disaster threats in coastal areas. It includes risk identification, good spatial planning, disaster-resistant infrastructure development, community education and emergency response preparedness. Cross-sector collaboration and community participation are also considered important in implementing this policy. The study also includes examples of integrated development policies implemented in Palu City in response to natural disasters that occurred in the region. The objective of this study is to reduce the risk of natural disasters through the implementation of integrated development policies.